Physical Fitness Level of Female Handball Athletes of the Special Sports School (SKO) of Riau Province - Makorohim, M Fransazeli (UNIB Press, 2025)
This study aims to determine the physical condition of female handball athletes at the Special Sports School (SKO) in Riau Province. Good physical condition is crucial for athletes, especially in sports like handball, which require speed, endurance, strength, and body coordination. This study used a quantitative descriptive method with an observational approach through a cross-sectional survey. The sample consisted of 14 female handball athletes at SKO in Riau Province. Data were collected using the Indonesian Physical Fitness Test (TKJI), which includes five components: a 60-meter run, a 60-second hang lift, a 60-second sit-down, a vertical jump, and a 1200-meter run. The results showed that the physical condition of female athletes was generally in the good (71.43%) and moderate (28.57%) categories. No respondents were in the poor or very poor categories. The best physical component was the sit-down test, with 78% in the good to excellent category. Aspects that need to be improved are the endurance and strength of the arm and shoulder muscles (64.28% in the moderate category) and explosive power of the legs (57.14% in the moderate to low category). These results indicate that the training program at the Riau Province SKO is quite effective, but improvements in upper-body strength and leg explosiveness training are needed to optimize athlete performance. Therefore, this study can serve as a reference for coaches and trainers at the Riau Province SKO in developing more specific, data-driven training programs to improve the physical fitness and performance of handball athletes at the regional and national levels.